2017
DOI: 10.1177/0891988717731827
|View full text |Cite
|
Sign up to set email alerts
|

Subjective-Objective Sleep Discrepancy in Older Adults With MCI and Subsyndromal Depression

Abstract: Background/Objectives We investigated the prevalence and correlates of discrepancies between self-reported sleep quality (Pittsburgh Sleep Quality Index) and objective sleep efficiency (actigraphy) in older adults with mild cognitive impairment (MCI) and subsyndromal depression. Methods This was a secondary analysis of a clincial trial with 59 adults aged 60 years and older with MCI and subsyndromal depression. We included baseline data on participants’ subjective sleep quality, objective sleep efficiency, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…self‐report recollection) of sleep quality. Previous comparisons of objective and subjective measures of sleep quality have shown that they are often discordant in older adults (DiNapoli et al, ; Landry, Best, & Liu‐Ambrose, ); thus, the degree to which PA is related to objective indices of sleep quality is unclear. Further, sleep quality and PA are often averaged over multiple days, which ignores day‐to‐day variation and limits the ability of the research to determine whether one behaviour influences the other from one day to the next (McGlinchey, Gershon, Eidelman, Kaplan, & Harvey, ).…”
Section: Introductionmentioning
confidence: 99%
“…self‐report recollection) of sleep quality. Previous comparisons of objective and subjective measures of sleep quality have shown that they are often discordant in older adults (DiNapoli et al, ; Landry, Best, & Liu‐Ambrose, ); thus, the degree to which PA is related to objective indices of sleep quality is unclear. Further, sleep quality and PA are often averaged over multiple days, which ignores day‐to‐day variation and limits the ability of the research to determine whether one behaviour influences the other from one day to the next (McGlinchey, Gershon, Eidelman, Kaplan, & Harvey, ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, 28.8% reported poor sleep quality but had good objective sleep efficiency. The correlation between objective sleep efficiency and perceived sleep quality in this sample was low (r = - 0.06; p = 0.64; DiNapoli et al, 2017). These results indicated a discrepancy between perceived and objective sleep, supporting using multiple sleep measures.…”
mentioning
confidence: 58%
“…DiNapoli et al (2017) reported that 61% of older adults (N = 59) had a discrepancy between perceived and objectively measured sleep-wake disturbances. Among these adults, 32.2% reported good perceived sleep quality but had poor objective sleep efficiency.…”
mentioning
confidence: 99%
“…However, MMSE scores did not correlate with subjective-objective differences suggesting that the discrepancy was not related to cognitive functioning as assessed by the MMSE [ 40 ]. Another study in 59 older adults with cognitive impairment and depression used an extensive battery of cognitive tests (including MMSE, CDR, and other dementia-specific tests) and found that delayed memory, but not level of executive functioning, was associated with increased discrepancy between actigraphy and the Pittsburgh Sleep Quality Index [ 39 ]. However, there have been several other studies that showed no effect of cognition as measured by MMSE or the Montreal Cognitive Assessment [ 31 , 33 ].…”
Section: Discussionmentioning
confidence: 99%